Translations of Vocabularies in Systems of Communicating Agents - van Eijk, M.; de Boer, F.S.; van der Hoek, W.; Meyer, J-J.Ch (Electronic notes in theoretical computer science, 1998)
We develop a programming framework for systems of agents that interact with each other in a shared environment. We model the common environment as a mathematical structure and assign to each agent a part of this environment as its expertise. This expertise is given by a syntactical signature composed of a collection of relation and function symbols, which gives rise to a window on the environment. The agents observe and manipulate their individual windows and additionally exchange information about them along interconnecting communication channels. During such communication steps the agents may introduce new mental concepts to act as translations of concepts from foreign signatures that are referred to in the information received. Finally, the agents maintain a private belief base, which together with their window on the environment constitutes their mental state. This all results in an abstract programming language of communicating agents, which incorporates and generalizes traditional programming concepts from the field of concurrency theory. The syntax for the language is given, followed by a semantical description in terms of a transition system. This system enables the formal derivation of computations and gives rise to an operational semantics of the multi-agent programming language.